LEADERSHIP ASSESSMENT OF LOCAL ADMINISTRATORS IN MUEANG NONTHABURI DISTRICT, NONTHABURI PROVINCE - Yangsuay , Thonghai (Journal of MCU Nakhondhat, 2023)
The objectives of this research were: 1) to study the level of leadership assessment of local administrators in Mueang Nonthaburi District, Nonthaburi Province, and 2) to study the recommendations for the development of leadership of local administrators in Mueang Nonthaburi District, Nonthaburi Province. This was quantitative research. The populations in this study were elector in Mueang Nonthaburi District, Nonthaburi Province 47,436 people. The determine sample group according to Taro Yamane’s table. A sample was 400 people. The research instrument was questionnaires. Data was analyzed using percentage, mean, and standard deviation. The results found that 1) the results of the study were the level of leadership assessment of local administrators in Mueang Nonthaburi District, Nonthaburi Province, were at a high level for overall. When considering each aspect, it was found that it was at a high level in all aspects. The highest average to the lowest as follows: Morality and ethics, were at a high level Secondly vision, characteristics, administration, responsibility and leadership, it was at a lowest level, and 2) the recommendations for leadership development of local administrators in Mueang Nonthaburi District, Nonthaburi Province, with the largest number was local administrators should allocate a budgets for local development all aspects. Secondly, local administrators should important for all people to be equal. Local administrators should visit to people for to know the problem and should allow people to participate in activities with the Sub-District Administrative Organization, respectively.